2015
DOI: 10.3389/fnint.2015.00039
|View full text |Cite
|
Sign up to set email alerts
|

Beyond reward prediction errors: the role of dopamine in movement kinematics

Abstract: We recorded activity of dopamine (DA) neurons in the substantia nigra pars compacta in unrestrained mice while monitoring their movements with video tracking. Our approach allows an unbiased examination of the continuous relationship between single unit activity and behavior. Although DA neurons show characteristic burst firing following cue or reward presentation, as previously reported, their activity can be explained by the representation of actual movement kinematics. Unlike neighboring pars reticulata GAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
120
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(138 citation statements)
references
References 75 publications
(125 reference statements)
17
120
1
Order By: Relevance
“…Prior work demonstrates that striatal MSNs and FSIs encode aspects of movement (Berke et al, 2004; Berke, 2008; Hernandez et al, 2013; Jin et al, 2014; Barter et al, 2015a, 2015b). To examine striatal function during dyskinesias, we recorded striatal neuronal ensembles and tracked movement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work demonstrates that striatal MSNs and FSIs encode aspects of movement (Berke et al, 2004; Berke, 2008; Hernandez et al, 2013; Jin et al, 2014; Barter et al, 2015a, 2015b). To examine striatal function during dyskinesias, we recorded striatal neuronal ensembles and tracked movement.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have largely relied on AIM scores, which can be laborious and temporally limited (Lundblad et al, 2004). Tracking techniques have been used to correlate movements with striatal neurophysiology (Barter et al, 2015a, 2015b), and here we extend this work to LIDs.…”
Section: Discussionmentioning
confidence: 96%
“…Under different experimental settings, nigrostriatal dopamine neurons have been suggested to encode the salience of stimuli (Matsumoto and Hikosaka, 2009), the value of cues in stimulus-response behavior (Kim et al, 2015; Morris et al, 2006), the initiation and termination of self-paced action sequences (Jin and Costa, 2010), and might even directly reflect movement kinematics (Barter et al, 2015). In the current study, mice were trained to dynamically select two alternative actions according to internally-monitored temporal information.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies with optical imaging have revealed that dopamine sends both reward- and movement-related information to the striatum, likely by different dopaminergic axons (Howe and Dombeck, 2016; Parker et al, 2016). Importantly, it has been further demonstrated that the movement-related signaling in dopaminergic axons is not only associated with but also capable of directly triggering movements, emphasizing a motor nature of the nigrostriatal dopamine system (Barter et al, 2015; Howe and Dombeck, 2016; Jin and Costa, 2010). Together with the current study, these results support functionally heterogeneous roles of dopamine signaling during behavior (Hamid et al, 2016; Kim et al, 2015; Schultz, 2007), acting at both fast and slow timescales (Hamid et al, 2016; Schultz, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some dopaminergic neurons respond to novel or salient events or during cognitive processes such as decision making and working memory (6,(8)(9)(10). Moreover, although the firing of these dopaminergic neurons generally has been thought not to vary consistently with movement (3,11), there is evidence that the activity of putatively classified dopaminergic neurons can change during movement execution in a heterogeneous manner (12)(13)(14)(15)(16). This evidence, in turn, raises the possibilities that at least some types of movement might be differentially encoded by the firing of distinct populations of dopaminergic neuron and that dysregulation of such activity might contribute to motor impairment in PD before, or commensurate with, frank neurodegeneration.…”
mentioning
confidence: 99%